Primary cardiac angiosarcoma - (:unkn) unknown (My University, 2001)
Primary malignant cardiac tumors are extremely rare neoplasms. About three-quarters of all cardiac tumors are histologically benign. A 24-year-old man presented to the hospital with dyspnea and chest pain. A solid, dense, nonhomogeneous and rough-surfaced mass (89 × 90 × 36 mm) with protrusion into the right heart cavities was observed on transthoracic echocardiography. The findings were confirmed by transesophageal echocardiography and magnetic resonance imaging. The histopathology of the mass confirmed a diagnosis of angiosarcoma. No evidence of an extracardiac origin of the tumor was found by radiological body imaging. The patient died 2 months after presentation to the hospital.
Keywords: Angiosarcoma; Cardiac tumor; Malignancy; Right atrium; Right ventricle